Development of a smart activity-based probe to detect subcellular activity of asparaginyl endopeptidase in living cells. Issue 38 (18th September 2017) - Hong, Jong-Ah; Choi, Na-Eun; La, Yeo-Kyoung; Nam, Ho Yeon; Seo, Jiwon; Lee, Jiyoun
Abstract : A smart activity-based probe that generates a turn-on fluorescence signal in response to enzyme activity was developed, allowing dynamic imaging of subcellular enzyme activity in living cells. Abstract : We developed a smart activity-based probe that detects the activity of asparaginyl endopeptidase (AEP) in live cells to monitor the dynamics of enzyme regulation. The newly designed probe generated a turn-on fluorescence signal in response to the activity of AEP in living cells without compromising the labelling efficiency or selectivity. Our probe closely reflected the enzyme activity in its native state, detecting subcellular AEP activity in colon cancer cells and neuronal cells.